REKONSTRUKSI PASAL 52 AYAT 2 PP NOMOR 35 TAHUN 2021 TENTANG PELANGGARAN BERSIFAT MENDESAK DALAM PEMUTUSAN HUBUNGAN KERJA - Pratama Erindo, Tri Mandala (Ensiklopedia Sosial Review, 2025)
This study aims to examine the conformity of Article 52 paragraph (2) of Government Regulation Number 35 of 2021 concerning termination of employment (PHK) due to urgent violations with the principle of equality before the law as regulated in Article 27 paragraph (1) of the 1945 Constitution. The focus of the problem lies in the potential conflict between this provision and the Constitutional Court Decision Number 012/PUU-I/2003 which annulled Article 158 of Law Number 13 of 2003 concerning Termination of Employment due to serious errors. This study uses normative legal research with a statutory and conceptual approach through analysis of primary, secondary, and tertiary legal materials. The results of the study indicate that Article 52 paragraph (2) of Government Regulation No. 35 of 2021 is not in line with the principles of justice, legal certainty, and protection of workers' rights because it gives unilateral authority to employers without a fair evidentiary mechanism. Therefore, this provision needs to be reconstructed to align with the principles of the rule of law and the Constitutional Court Decision. The government also needs to clarify the criteria for urgent violations and require that layoffs be determined through the Industrial Relations Court.Keywords: layoffs, urgent violations, legal reconstruction.